Evaluating exposure of northern fur seals, Callorhinus ursinus, to microplastic pollution through fecal analysis. (January 2019) - Donohue, Mary J.; Masura, Julie; Gelatt, Thomas; Ream, Rolf; Baker, Jason D.; Faulhaber, Kayleigh; Lerner, Darren T.
Abstract: Environmental microplastics are widely documented in marine life and bioaccumulation may present risks to marine predators. Investigations of microplastics in marine mammals are increasing, though none have examined animals routinely consumed by humans. Here, we investigate microplastic exposure in the northern fur seal ( Callorhinus ursinus ), a species consumed by humans, using fecal material. We examined 44 feces (scat) at sites encompassing the seals' eastern Pacific range. Multiple contamination control measures were implemented, including field and laboratory controls. Fragments were the most common microplastic recovered, in 55% (24/44) of scat and no controls (range 1 to 86 fragments/scat, mean 16.6, sd 19.1). Microplastic fibers were recovered from 41% of scats (18/44), though some controls contained fibers confounding fiber results. Fecal analysis documented northern fur seal exposure to microplastics throughout their eastern Pacific range. Graphical abstract: Unlabelled Image Highlights: Wild northern fur seals are exposed to microplastics throughout their U.S. range. Over 50% of northern fur seal feces contained from 1 to 86 microplastic fragments. Threats associated with microplastics are incompletely known. Microplastic bioaccumulation in marine top predators represents an emerging risk.